Relationship Between Fraud Auditing and Forensic Accounting - Atağan, Gülşah; Kavak, Aylin (International Journal of Contemporary Economics and Administrative Sciences, 2018)
In the study, the survey were applied to the work groups registered to the members of Chamber of Certified Public Accountants in Aydın. 193 members of the profession were reached. Their ideas were consulted about fraud auditing and forensic accounting. It was tried to fraud the reasons for fraud of the individuals and the companies, the people who fraud more and the behavioral charasteristics of the fraudsters. It was also mentioned about the regulations in our counrty and in the World about fraud and the issue, how effective these regulations, were studied were. The precautions and tools to find out the fraud and to prevent them were evaluated. Besides, the knowledge of the members of the profession were consulted about in which fields forensic accounting serve, the contributions to the avaiable profession, the participation into the inspectorial process and its effects. The gathered information as a result of the survey were analysisedwith the program SPSS for Windows 22.0. The test Man-Whitney-U was used for the analysis of the information between two indepent groups, the test Kruskall Whallis was used for comperation of the information among more than two indepent groups. The test Man-Whitney-U was used for the analysis of the differences as a follow-up of the test Kruskall Whallis.